Incidence and Pattern of Patient-Perceived Oral Medicine Emergencies during Lockdown: Experience of Tertiary Health Care Centre of Eastern Nepal - Regmee, P.; Adhikari, S.; Sulu, S.; Rimal, J.; Maharjan, I. K. (Kathmandu University Medical Journal, 2022)
Background There has been a significant drop in the number of patients seeking oral medicine care during the lockdown period. Objective To find the incidence and pattern of patient perceived oral medicine emergencies in the tertiary healthcare centre of eastern Nepal, during the lockdown period. Method The clinical profile of patients seeking oral medicine care between 30th April 2021 to 25th June 2021 (period of strict lockdown in Sunsari district) was recorded. Data were recorded in an excel sheet and transferred to Statistical Package for the Social Sciences version 11.5. Frequency and proportion were calculated. Result During the lockdown, 300 patients had visited the hospital with different oral diseases seeking the care of an oral physician. The average number of patients seeking oral medicine care per day was approximately six. Of the total patients, 110 patients had pain as their chief complaint, 48 had wound and 34 had a burning sensation in the mouth. Among them 82% perceived their complaint as an emergency. The provisional diagnosis was temporomandibular disorders in 40 patients, trigeminal neuralgia in 38 patients and 34 had carcinoma. Conclusion Patients seeking oral medicine care during the lockdown period had decreased by about one-third. Pertaining to oral medicine, pain in any orofacial area was the most common patient perceived emergency condition followed by wound and burning sensation. Maximum number of patients visiting the department perceived their complain as an emergency.